Implementation of Competent Human Resource Management in Improving the Professionalism of Teachers of SDN. - Hari Irawan (Pustaka Digital Indonesia, 2022)
This study aims to determine the application of competent human resource management in improving the professionalism of SDN teachers in Kalaena sub-district, East Luwu district (study at SDN 156 Kalaena). This type of research used in this research is case research with a qualitative descriptive approach. The processed data is the result of interviews from informants, namely the principal and teachers at SDN 156 Kalaena. The data collection techniques used were interview observation and documentation. The data analysis technique was carried out by means of data reduction and drawing conclusions. Based on the results of research carried out by researchers, the conclusion that can be drawn is that human resources at SDN 156 Kalaena can be categorized as good or adequate both in quantity and quality Efforts to improve teacher professionalism at SDN 156 Kalaena have been well done in terms of understanding protest demands to achieve qualifications and competence, building good and broad nursing relationships through professional organizations developing ethos and adopting innovations in the use of communication and information technology The implementation of human resource management by the principal of SDN 156 Kalaena has been carried out well, especially in terms of placement of human resources training and development of human resources assessments of performance using qualitative and quantitative assessments and compensation for incentives.